Colorectal anastomosis dehiscence - a solution with quality of life – Case Report - Amado, Fabíola; Ferreira, Alexandra; Lamas, Marta; Cortez, Luis (Brazilian Journal of Case Reports, 2024)
Rectal cancer is the fifth most frequent neoplasm in both sexes in Portugal. Anterior rectal resection has become the gold standard in the treatment of this condition and surgical treatment is the only cure. The rate of low rectal anastomotic leak (AL) is approximately 10% of all ALs in colorectal surgery. Management of AL is variable and could be challenging. Endo-SPONGE (a type of endoscopic vacuum therapy (EVT)) has been applied in the management of ALs after colorectal surgery. In the literature, EVT has been shown to accelerate wound healing by increasing local blood flow, reducing bacterial load and stimulating the growth of granulation tissue; it has the advantages of being less invasive than surgery, reducing hospital stay time and reducing the risk of complications; however, it can present some risks such as bleeding, infection, intestinal perforation and intestinal obstruction. In this paper, we describe EVT as a method for treating AL after rectal resection that appears to be a minimally invasive, safe and effective treatment modality for patients with a significant colorectal leak without any generalized peritonitis with high clinical and technical success rates.